Problemy funkcjonowania rynku wewnętrznego UE w świetle polityki konkurencji - Burzyński, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Economic integration in the European Union market is a long process, constantly evolving and bringing calculable economic benefits. Existence of the internal market in the EU structures, formed over several years, is conducive primarily to a social market economy with high competitiveness, aiming at full employment and social progress. Each country applying for accession to the EU should understand and accept these assumptions, as well as unconditionally adhere to them. The EU competition policy, defining the legal framework for free competition, although it may sometimes be contrary to the national interest of Member States, should be strictly respected. Despite many years of experience, EU countries still face problems which in consequence disrupt the functioning of the principles of this policy. Contemporary examples of state aid for either direct or indirect support of the economic entities are the best proof of this. For the proper development of the internal market it is necessary for all the member states to adhere to the principles of this policy. Only in this way does the European Union stand a chance to become an area of greater economic competitiveness, and can thus compete with the biggest economies in the world.
Keywords: integracja europejska; polityka konkurencji UE; rynek wewnętrzny; pomoc państwa; handel międzynarodowy